INCREASING ORAL COMMUNICATION SKILLS IN READING CLASSES BY READING TO ACT - Wienny Ardriyati (Universitas Stikubank (UNISBANK) Semarang, 2010)
This research is about one of the methods in teaching English in Reading Class in Language Faculty at University of Stikubank. It aimed at using an interactive method to improve oral communication skills. It is a qualitative research and employs five data collection methods, namely: class observation, teaching journal, document collection, questionnaire and interview. The population was the language students of STIKUBANK University. There were thirty one students. They attended the Reading Class in the semester. They read a narrative text, find out the roles then they act based on the plot of the narrative text. The results show that the students are highly motivated to have a role play as one of the methods used in reading class. They feel that they get enough practice to use English actively besides their understanding in reading a narrative text. The process of reading the text is satisfactory. The students can understand the plot and they can transfer it into a scenario of a play. Having got the scenario the students perform their play with enjoyable performances. Their oral communication in acting the role is tolerable too. Thus, reading to act by a role play can be used a Reading Class. In addition, it is suggested that in reading class the lecturer should give another interactive method besides a role play. She or he may apply many different activities to make a reading class more interactive. Keywords: role play, plot, scenario, action research, teaching journal.